Comparative Investigation on Coffee Cascara from Dry and Wet Methods: Chemical and Functional Properties - Paz Cano-Muñoz; Miguel Rebollo-Hernanz; Cheyenne Braojos; Silvia Cañas; Alicia Gil-Ramirez; Yolanda Aguilera; Maria A. Martin-Cabrejas; Vanesa Benitez (Biology and Life Sciences Forum, 2021)
Coffee processing involves the separation of its different structures that are considered by-products. There is a current interest in adding new value to coffee by-products through their conversion into food ingredients. Following a biorefinery approach, coffee by-products can produce phenolic and caffeine-rich extracts and water-insoluble residues (WIRs) rich in dietary fiber. Consequently, this work aimed to study the flour and the WIR (obtained through a sustainable and optimized aqueous extraction of phenolic compounds) from the main by-product of coffee processing, the coffee cascara, investigating the chemical and functional differences among ingredients obtained from the dry and wet processing methods. Both dry and wet cascaras (in flour and WIR) presented a high dietary fiber content (46–97%), especially outstanding in the WIRs. Soluble dietary fiber was 2.2 to 3.6-fold higher (p < 0.05) in flours than in WIRs. The wet coffee cascara flour exhibited a remarkable antioxidant capacity (2.4 to 4.2-fold higher than the other products), as well as adequate techno-functional and physicochemical properties. All by-products inhibited α-amylase (62–96%) and reduced starch hydrolysis (52–97%), which was associated (r = 0.965, p < 0.05) with the differential total phenolic content found in samples (6.1–40.4 mg gallic acid equivalents per gram). Similarly, coffee cascara-based ingredients showed pancreatic lipase inhibitory properties (54–65%) and reduced the intestinal absorption of cholesterol (50–88%) and bile salts (81–90%) in vitro. In conclusion, both dry and wet coffee cascara exhibit a similar chemical composition and functional properties and could be revalued as new sustainable ingredients (flours and WIRs, and phenolic-rich extracts) following a biorefinery approach. These coffee cascara-based ingredients may exhibit beneficial health properties reducing oxidative stress and glucose and lipid absorption.